Analysis of Acute Postoperative Pain in Patients undergoing Transabdominal Preperitoneal (TAPP) Repair of Inguinal Hernia in Manipal Teaching Hospital - Shrestha, Binod Bade; Shrestha, Sujan (Nepal Journal of Medical Sciences, 2020)
Background: Laparoscopic inguinal hernia repair in adults require the use of prosthetic material. We aimed to investigate the acute postoperative pain in patients who underwent transabdominal preperitoneal inguinal hernia repair using heavy or light weight polypropylene mesh. Methods: This observational, analytical study was conducted in172 adult patients, aged 18-80 years, who underwent transabdominal preperitoneal inguinal hernia repair from January 2017 - October 2019. The patients were divided into two groups as HWM group (heavyweight polypropylene mesh), n=81 and LWM group (light weight polypropylene mesh) n=91. The patients in both the groups were compared in terms of acute postoperative pain at 24 and 48 hours using visual analogue scale (VAS) score. Results: The visual analogue scale (VAS) score of HWM group and LWM group at 24 hours was 5.42 ± 1.25 and 4.46 ± 1.61 respectively (p=0.00). The VAS score at 48 hours was 3.44 ± 1.07 and 2.74 ± 1.27 for HWM and LWM group respectively (p=0.00). Conclusions: The post-operative pain at 24 and 48 hours following transabdominal preperitoneal inguinal hernia repair using light weight polypropylene mesh was less as compared to the patients whose hernia were repaired using heavy weight polypropylene mesh.